Characterization and Immunological Activity of Exopolysaccharide from Lacticaseibacillus paracasei GL1 Isolated from Tibetan Kefir Grains - Xiaomeng Wang; Juanjuan Tian; Xueliang Zhang; Nanyu Tang; Xin Rui; Qiuqin Zhang; Mingsheng Dong; Wei Li (Foods, 2022)
Two exopolysaccharide fractions (GL1-E1 and GL1-E2) of Lacticaseibacillus paracasei GL1 were isolated with the molecular weights of 3.9 × 105 Da and 8.2 × 105 Da, respectively. Both fractions possessed mannose, glucose, and galactose in molar ratios of 1.16:1.00:0.1, and 3.81:1.00:0.12, respectively. A structural arrangement of two fractions was proposed by methylation, one-dimensional and two-dimensional nuclear magnetic resonance experiments. The backbone of GL1-E1 consisted of →4)-α-D-Glcp(1→, →3,4)-α-D-Manp(1→, →3,6)-α-D-Manp(1→, →6)-α-D-Manp(1→, and →6)-α-D-Galp(1→ with α-D-Glcp at branching point. The backbone of GL1-E2 consisted of →4)-α-D-Glcp(1→, →3,4)-α-D-Manp(1→, →3,6)-α-D-Manp(1→, →6)-α-D-Manp(1→, →6)-α-D-Galp(1→, and →4)-β-D-Manp(1→, and the side chain also consisted of α-D-Manp residue. In addition, the differential scanning calorimetry (DSC) analysis indicated that both GL1-E1 and GL1-E2 had good thermal stability. Furthermore, the two fractions could promote the viability of RAW264.7 cells and exert an immunomodulatory role by enhancing phagocytosis, increasing nitric oxide (NO) release and promoting the expression of cytokines.